Clinical Outcomes of Drug-Coated Balloon Treatment After Successful Revascularization of de novo Chronic Total Occlusions - Jun, Eun Jung; Shin, Eun-Seok; Teoh, Eu-Vin; Bhak, Youngjune; Yuan, Song Lin; Chu, Chong-Mow; Garg, Scot; Liew, Houng Bang (Frontiers in Cardiovascular Medicine, 2022)
Background: The safety and efficacy of drug-coated balloon (DCB) treatment for de novo coronary chronic total occlusion (CTO) remain uncertain. The aim of this study was to evaluate the outcomes of DCB only treatment for de novo CTO. Methods: In this retrospective study, 101 vessels with de novo CTO lesions dilated by balloon angioplasty with thrombolysis in myocardial infarction flow grade 3 were included. Among them, 93 vessels successfully treated with DCB only treatment was analyzed. The study endpoint was major adverse cardiac events (MACE) at 2-year, a composite of cardiac death, non-fatal myocardial infarction (MI), target vessel revascularization (TVR), and target vessel thrombosis. The secondary endpoint was late lumen loss (LLL) on follow-up coronary angiography. Results: All 84 patients were followed up clinically, and 67 vessels underwent scheduled coronary angiography after 6-month. There were no procedural complications, and three vessels required bailout-stenting. The median follow-up was 720 days (interquartile range [IQR]: 406 to 1,268 days). MACE occurred in 8.3% of the patients after 1 year, including cardiac death (1.2%), TVR (7.1%), and no non-fatal MI and target vessel thrombosis. Two years after treatment, MACE occurred in 16.7% of the patients, including cardiac death (2.4%), non-fatal MI (3.6%), TVR (13.1%), and no target vessel thrombosis. The mean LLL was 0.03 ± 0.53 mm. Binary restenosis occurred in 14.9% of the treated vessels, and 3.0% of the vessels had late re-occlusion on follow-up coronary angiography. Conclusions: If the result of revascularization using balloon angioplasty is good, the clinical outcomes of DCB only treatment of de novo CTOs at the 2-year follow-up are encouraging, with a low rate of hard endpoints and acceptable MACE rates (Clinical Trial Registration Information: Impact of Drug-coated Balloon Treatment in de Novo Coronary Lesion; NCT04619277).